2022
DOI: 10.1002/cplu.202200199
|View full text |Cite
|
Sign up to set email alerts
|

Structural Consequences of N‐Methylation of N‐Terminus in Oligourea Foldamers

Abstract: Oligourea foldamers fold into 2.5‐helices. Most of the known modifications of the backbone, such as NH or CO group substitutions or incorporations of non‐canonical residues, do not change the conformational properties of the resulting oligourea oligomers. In this study, we examined the structural influence of the methyl group, substituting NH protons in one or two residues at the N‐terminus of the foldamer. Such N‐methylated oligoureas appear to be helically folded with helix parameters determined from the cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Based on ROESY spectra, it was confirmed that all urea groups of the oligourea hydantoin and oligourea acid are in trans,trans conformations (see the Supporting Information, Figure S48 ), known to be necessary for helical folding of the backbone. Additionally, strong ROE connectivity between CH 3 (tBu) and both N’H(Ala2u) and NH(Ala3u) was observed, further supporting the formation of a 2.5 helix [ 22 ].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on ROESY spectra, it was confirmed that all urea groups of the oligourea hydantoin and oligourea acid are in trans,trans conformations (see the Supporting Information, Figure S48 ), known to be necessary for helical folding of the backbone. Additionally, strong ROE connectivity between CH 3 (tBu) and both N’H(Ala2u) and NH(Ala3u) was observed, further supporting the formation of a 2.5 helix [ 22 ].…”
Section: Resultsmentioning
confidence: 97%
“…Over the years the (oligo)urea backbone has undergone various modifications and the impact of these changes on the structural properties of the new analogs has been investigated. This has led to the conclusion that the 2.5-helical structures of oligoureas are robust and it is possible to substitute the urea residue with γ-amino acid [ 6 , 18 ], carbamate [ 18 , 19 ], thiourea [ 20 ], guanidinium [ 21 ] and also N-methylated [ 22 ] or urea residues with noncanonical substitution patterns [ 23 ] without the loss of the structural integrity of the new molecule. It has also been shown that urea fragments as short as three residues can induce a helical conformation when fused to a peptide too short to fold into a stable secondary structure [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%